Kekerasan mikro enamel gigi permanen muda setelah aplikasi bahan pemutih gigi dan pasta remineralisasi (Enamel micro hardness of young permanent tooth after bleaching and remineralization paste application) - Budianto Liwang; Irmawati Irmawati; Els Budipramana (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2014)
Background: Studies showed that bleaching agent had demineralization effect to enamel, and encourage use of remineralization paste after bleaching treatment especially in young permanent tooth which in post-eruptive enamel maturation. Purpose: The study ere aimed to determine the bleaching agent effect on enamel surface micro hardness, and to determine the effect of remineralization paste application on enamel surface micro hardness of young permanent tooth after bleaching treatment. Methods: Fourteen young permanent teeth were placed in a block of resin with a window on the buccal surface enamel. The initial enamel surface hardness was measured using Microvickers Hardness Tester. Then the application of hydrogen peroxide bleaching materials 30% was done three times for 15 minutes and followed by surface hardness of enamel measurement. Samples were divided into 2 groups; the first group was applied paste of Hydroxy apatite + NaF 1450ppm , and the second group was applied paste of CPP–ACP + NaF 900ppm. Each paste was applied for 30 minutes for 7 days, then the enamel surface hardness of samples were measured. Results: The enamel surface micro hardness decreased after bleaching from 333.09 ± 10.49 VHN to 299.15±5.70 VHN. Micro hardness after application of Hidroxy apatite + NaF 1450ppm was 316.61±5.87 VHN and after application of CPP-ACP + NaF 900ppm was 319.94±3.25 VHN, however the micro hardness still lower than initial micro hardness. Conclusion: Tooth bleaching agent caused a decrease of enamel surface micro hardness in young permanent tooth. The use of remineralization paste enabled to increase the enamel surface micro hardness young permanent tooth.Latar belakang: Penelitian-penelitian sebelumnya menunjukkan bahwa produk pemutih gigi memiliki efek demineralisasi enamel gigi, dan mendorong penggunaan pasta remineralisasi setelah pemutihan gigi terutama di gigi muda permanen yang enamelnya masih dalam proses maturasi pasca-erupsi. Tujuan: Penelitian ini bertujuan untuk meneliti kekerasan mikro permukaan email gigi permanen muda, dan efek aplikasi pasta remineralisasi setelah pemutihan gigi. Metode: Empat belas gigi permanen muda ditempatkan dalam blok resin dengan jendela pada enamel permukaan bukal dan dilakukan pengukuran kekerasan permukaan enamel sampel awal dengan menggunakan alat Microvickers Hardness Tester. Kemudian dilakukan aplikasi bahan bleaching hidrogen peroxide 30% sebanyak 3 kali masing-masing selama 15 menit. Setelah aplikasi bahan bleaching, kekerasan permukaan enamel sampel diukur kembali. Sampel dibagi 2 kelompok; kelompok pertama diaplikasi pasta remineralisasi Hidroksi apatit + NaF 1450ppm, dan kelompok kedua diaplikasi pasta CPP-ACP + NaF 900ppm. Masing-masing pasta tersebut diaplikasikan selama 30 menit 7 hari berturut-turut. Setelah aplikasi pasta remineralisasi, sampel diukur kembali kekerasan permukaan enamelnya. Hasil: Kekerasan mikro permukaan enamel menurun setelah aplikasi pemutih gigi, dari 333.09 ± 10.49 VHN ke 299,15 ± 5.70 VHN. Kekerasan mikro setelah aplikasi Hidroxy apatit + NaF